2019
DOI: 10.20858/sjsutst.2019.104.4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Impact of Non-Parallelism of Shafts' Axes on the Contact Area of Cooperating Teeth and Gearbox's Components Vibrations

Abstract: In this article, the results of experimental research and simulation studies using a geometric model made in CAD software were presented. The aim of the conducted research and simulations was to determine the influence of nonparallelism of shafts' axes on gearbox vibroactivity and the contact area of the cooperating teeth. The results showed that the change of the non-parallelism of shafts' axes significantly affects the vibrations of selected components of the operating gearbox and the contact area of coopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Another solution used to reduce the vibroactivity of gear transmissions is increasing the workmanship precision of transmission housings [2], particularly with regard to shaft alignment. Based on an analysis of the results obtained in experimental tests, Juzek [31] concluded that misalignment of the transmission shaft axles and its change in the course of tests exerts a significant impact on level of vibrations recorded on the transmission components. In that case, depending on the position of the fixed axle bearing, the differences in the RMS values of vibration signals reached up to several dozen per cent.…”
Section: Angeles and Kumralmentioning
confidence: 99%
“…Another solution used to reduce the vibroactivity of gear transmissions is increasing the workmanship precision of transmission housings [2], particularly with regard to shaft alignment. Based on an analysis of the results obtained in experimental tests, Juzek [31] concluded that misalignment of the transmission shaft axles and its change in the course of tests exerts a significant impact on level of vibrations recorded on the transmission components. In that case, depending on the position of the fixed axle bearing, the differences in the RMS values of vibration signals reached up to several dozen per cent.…”
Section: Angeles and Kumralmentioning
confidence: 99%